Tourism, terrorism and socio-economic crisis. The case of Perú (1980-1992) - Armas Asín, Fernando (2021)
The article underlines the importance of a proper distinction between the causes that could affect tourism in a country that goes though violent situations, economic crisis, and other combined problems, for a long period of time. Through the study of the Peruvian case, the work seeks to establish which elements were the most meaningful in affecting their receptive tourism between 1980 and 1992. Against what is commonly thought, it poses that the economic crisis as well as other social and political factors, together with the terrorism, were elements to consider, and not only the latter.